Analysis of the effect of GCG quality on the financial performance of Islamic banks - Flowurrence Wibawanti Dewany (STIE Perbanas Surabaya, 2015)
This research aims to know the effect of the quality of Good Corporate Governance implementation on the rate of return, measured using Return on Assets (ROA), the risk of financing, measured using Non Performing Financing (NPF), and capitals measured using Capital Adequacy Ratio (CAR) on Islamic Banks in Indonesia. The sampling technique used in this research is purposive sampling method with the limi-tation of Islamic Banks registered in Bank Indonesia, publish annual report and dis-close reports of Good Corporate Governance from 2010 to 2013. The result shows that the quality of Good Corporate Governance implementation on Islamic banks in Indo-nesia is categorized good, based on the composite mean value of 1.70676. The quality of Good Corporate Governance implementation has no effect on the rate of return and the risk of financing, but it has an effect on the capital.